REDESAIN WEBSITE UPT PERPUSTAKAAN UNIVERSITAS SEBELAS MARET SEBAGAI MEDIA PENDIDIKAN PENGGUNA BAGI PEMUSTAKA - Tri Hardian Satiawardana (Central Library of Universitas Sebelas Maret, 2016)
Library website is one of the information retrieval media for students who are in the academic environment. Library website thus should adapt to the needs of students especially in conducting research. This study aimed to analyze the effectiveness of the Sebelas Maret University Library website (UNS) as library education media after the redesign. Redesigning the website focuses on how to present the information sources in which the collections of UNS Library either in printed or electronic form exists. The results of the analysis after redesigning the website showed that the use of the website is as expected. This is showed through the statistics of the web pages most frequently accessed, the number of visitors, time spent from new visitors and returning visitors to visit the Library website UNS, user behavior -especially switching between web pages- and device platform used by a visitor to visit the Library website UNS. As a conclusion, after the redesign, UNS Library website is capable of facilitating student learning behavior that is independent, techie and mobile.